Revision of the leafhopper genus Dusuna Distant (Hemiptera: Cicadellidae: Ledrinae), with description of one new species from China - Sun, Jing; Webb, Mick; Zhang, Yalin (Zootaxa, 2014)
The leafhopper genus Dusuna Distant is revised to include seven species including one new species D. anacantha sp. nov. from China and one new combination D. distanti (Schmidt) n. comb. All species are described and illustrated. A checklist to species of the genus is provided together with a key to separate the two species known from the male. Figures of an unknown species from Malaysia (possibly new) are also included.